Inhomogeneity detection within a head-sized phantom using tracking of charged nuclear fragments in ion beam therapy - Félix-Bautista, Renato; Ghesquière-Diérickx, Laura; Ochoa-Parra, Pamela; Kelleter, Laurent; Echner, Gernot; Debus, Jürgen; Jäkel, Oliver; Martišíková, Mária; Gehrke, Tim (Physics in medicine and biology, 2024)
Objective. The highly conformal carbon-ion radiotherapy is associated with an increased sensitivity of the dose distributions to internal changes in the patient during the treatment course. Hence, monitoring methodologies capable of detecting such changes are of vital importance. We established experimental setup conditions to address the sensitivity of a monitoring approach based on secondary-fragment tracking for detecting clinically motivated air cavity dimensions in a homogeneous head-sized PMMA phantom in 40 mm depth. Approach. The air cavities were positioned within the entrance channel of a treatment field of 50 mm diameter at three lateral positions. The measured secondary-fragment emission profiles were compared to a reference measurement without cavities. The experiments were conducted at the Heidelberg Ion-Beam Therapy Center in Germany at typical doses and dose rates. Main results. Significances above a detectability threshold of 2σ for the larger cavities (20 mm diameter and 4 mm thickness, and 20 mm diameter and 2 mm thickness) across the entire treatment field. The smallest cavity of 10 mm diameter and 2 mm thickness, which is on the lower limit of clinical interest, could not be detected at any position. We also demonstrated that it is feasible to reconstruct the lateral position of the cavity on average within 2.8 mm, once the cavity is detected. This is sufficient for the clinicians to estimate medical effects of such a cavity and to decide about the need for a control imaging CT. Significance. This investigation defines well-controlled reference conditions for the evaluation of the performance of any kind of treatment monitoring method and its capability to detect internal changes within head-sized objects. Four air cavities with volumes between 0.31 cm3 and 1.26 cm3 were narrowed down around the detectability threshold of this secondary-fragment-based monitoring method.
Online veröffentlicht: 6. November 2024
Gesehen am 25.06.2025